Sleep quality and creativity in Chinese college student during the COVID-19 pandemic: The mediating role of executive function - Guo, Botang; Song, Yue; Zhao, Lu; Cheng, Xinhui; Ma, Hanze; Qiu, Xiaohui; Yang, Xiuxian; Qiao, Zhengxue; Zhao, Erying; Bu, Tianyi; Yang, Jiarun; Mishra, Rupam; et al. (Frontiers in Public Health, 2022)
Background COVID-19 has impacted adolescents' interpersonal relationships, life attitudes, and mental health during the past 3 years. However, previous studies predominantly focused on negative problems, while few studies assessed the situation of teenagers from the perspective of positive psychology. Therefore, this study explores the creativity level of Chinese college students during the COVID-19 pandemic, the relationship between sleep quality and creativity, and the mediating role of executive function. Method A cross-sectional study was conducted across six colleges in Heilongjiang in China, with a sample of 4,258 college students recruited via stratified cluster sampling. Data were collected through an online survey. A mediation model was constructed, and SPSS PROCESS macro was used to analyze the data. Results The creativity score of Chinese college students during the COVID-19 pandemic was 106.48 ± 13.61. Correlation analysis demonstrated that sleep quality correlated negatively with creativity (r = −0.08, P < 0.01) but positively with executive function (r=0.45, P < 0.01), whilst executive function correlated negatively with creativity (r = −0.10, P < 0.01). Moreover, the mediation model revealed that executive function partially mediated the relationship between sleep quality and creativity in college students (indirect effect = −0.017, SE = 0.004, 95% CI = [−0.025, −0.008]). Executive function accounted for 48.6% of the variance in college students' creativity. Conclusion School administrators should implement measures such as sleep education to enhance students' sleep quality. Concurrently, curriculum and assessment implementation should enhance executive function. Such measures can contribute to improved student creativity, thus helping students overcome the negative emotional impact of the COVID-19 pandemic.